Predation shapes behavioral lateralization: insights from an adaptive radiation of livebearing fish. (23rd August 2021) - Hulthén, Kaj; Heinen-Kay, Justa L; Schmidt, Danielle A; Langerhans, R Brian
Abstract: Hemispheric brain lateralization can drive the expression of behavioral asymmetry, or laterality, which varies notably both within and among species. To explain these left–right behavioral asymmetries in animals, predator-mediated selection is often invoked. Recent studies have revealed that a relatively high degree of lateralization correlates positively with traits known to confer survival benefits against predators, including escape performance, multitasking abilities, and group coordination. Yet, we still know comparatively little about 1) how consistently predators shape behavioral lateralization, 2) the importance of sex-specific variation, and 3) the degree to which behavioral lateralization is heritable. Here, we take advantage of the model system of the radiation of Bahamas mosquitofish ( Gambusia hubbsi) and measure behavioral lateralization in hundreds of wild fish originating from multiple blue holes that differ in natural predation pressure. Moreover, we estimated the heritability of this trait using laboratory-born fish from one focal population. We found that the degree of lateralization but not the particular direction of lateralization (left or right) differed significantly across high and low predation risk environments. Fish originating from high-predation environments were more strongly lateralized, especially females. We further confirmed a genetic basis to behavioral lateralization in this species, with significant additive genetic variation in the population examined. Our results reveal that predation risk represents one key ecological factor that has likely shaped the origin and maintenance of this widespread behavioral phenomenon, even potentially explaining some of the sex-specific patterns of laterality recently described in some animals. Abstract : What explains the diversity of behavioral lateralization, like human handendness, across animals? We show that predation risk is one cause. Bahamas mosquitofish in high-predation environments (especially females) were more strongly lateralized than those in low-predation environments. We confirmed a genetic basis to these behavioral side biases. Tradeoffs between different abilities may explain the differentiation: e.g., stronger lateralization may increase task efficacy and facilitate evasion of predators, while reduced lateralization may provide competitive or social advantages.